University Nature Trails as Experiential Tools for Shaping Student Sustainability Attitudes: A Case Study from the University of Sopron (Hungary) - Andras Polgar; Veronika Elekné Fodor; András Náhlik; Dóra Németh; Márton Tóth; Árpád Őrsi; Enikő Pásztor; Ferenc Lakatos; Attila Fábián (Journal of Sustainability Perspectives, 2025)
University nature trails are innovative forms of experiential learning and environmental education that foster sustainability awareness, student engagement, and well-being. This study examines the impact of the nature trail located on the campus of the University of Sopron on students’ sustainability-related attitudes and behaviors. The research applies a mixed-methods approach: narrative and institutional case studies are complemented by a quantitative survey with 916 valid responses. The case study presents the conceptual background of the trail, its design and implementation process, and its integration into the university’s educational and community life. It highlights the cultural and local significance of the trail, as well as its connection to the sustainability efforts of higher education in Central Europe. The quantitative survey assesses students’ knowledge, confidence in applying sustainability principles in practice, and opinions on the university’s environmental initiatives (e.g., selective waste collection, use of renewable energy sources, and green infrastructure). The findings indicate a high level of interest in environmental issues among students, yet gaps remain in translating sustainability knowledge into consistent, everyday actions. The case study reveals that the trail provides a place-based, experiential learning environment that strengthens emotional bonds with nature, supports interdisciplinary learning, and fosters community engagement. By linking theoretical knowledge with direct experiences, it enables deeper understanding and helps bridge the gap between knowledge and action. The combined methodological approach offers a comprehensive view of how experiential learning environments can influence sustainability awareness. The study presents a Central European example in which sustainability education is embedded in local values and a nature-based setting, supporting behavioral change and community building in higher education.